MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES FOR THE PROFESSIONAL TRAINING OF FUTURE TEACHERS - Viacheslav Osadchyi (National Academy of Educational Sciences of Ukraine, 2019)
The role of information and communication technologies in the professional training of future teachers is determined in the paper. The purpose of the article is to understand the problem of the application of modern information and communication technologies and to identify ways of their use in the professional training of future teachers. It defines such modern information and communication technologies for the professional training future teachers: Internet resources and services, systems of educational content management, social services and networks, mobile technologies, artificial intelligence technologies, multimedia, cloud technologies, and mass open distance courses. The article presents the analysis and description of possibilities of software for its application in the teacher professional activity. The usage of the educational content management system at educational institutions in the world and in Ukraine is outlined. The conclusion is made about the expediency of their systematic use through introduction and improvement of the implemented system of information and technological support, which includes professional and pedagogical, technical, managerial, criteria and productive such subsystems, in the professional training of future teachers at pedagogical universities.